Sharia Economic Development in the Perspective of Evolution of Meaning and New Paradigm - Ahmad Salam; Diana Latipah; Karyono Karyono (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Sharia economic development faces epistemological challenges in responding to global changes and the growing demand for more inclusive and sustainable development models. The misalignment between the foundational pillars of Islamic economics and current planning practices highlights the need for a reinterpretation of development concepts. This study aims to examine the evolution of meaning and identify emerging paradigms in Sharia economic development, while reconstructing the relationship between its core pillars and strategic planning approaches. Employing a conceptual literature review method, the study systematically analyzes scholarly works from diverse primary and secondary sources. The findings reveal a shift from legal-normative interpretations toward value-based paradigms rooted in maqashid al-shariah and sustainability. Newly identified paradigms include spiritually-driven welfare development, structural justice, and the integration of maqashid with the Sustainable Development Goals (SDGs). This study contributes to the theoretical enrichment of Islamic economic development and provides a conceptual foundation for more contextual and transformative policy design.